Palamas and Florensky: The Metaphysics of the Heart in Patristic and Russian Philosophical Tradition - Kroczak, Justyna (Studia Ceranea, 2013)
Тhis paper focuses on the philosophical issue known as the metaphysics of the heart within Orthodox Christianity – both Russian and Byzantie versions. Russian religious thought is based on patristic tradition. Influences and connections can be seen in Florensky’s philosophy of All-Unity. This Russian philosopher was highly inspired by Gregory Palamas, fourteenth-century Eastern Church. These two Orthodox thinkers, mainly their metaphysics of heart are objects of interests.